Pembuatan Konfigurasi SSL yang Aman untuk Diimplementasikan pada Apache dan Nginx - Eka Wijaya Budihardjo; Lily Puspa Dewi; Agustinus Noertjahyana (Jurnal Infra, 2021)
Exploitation of a web server is a form of behavior of someone who takes advantage of a software vulnerability or security weakness. Exploitation of the web server can be in the form of Zombie Poodle, Golden Doodle, Poodle, and others. In addition, there are also man-in-the-middle-attacks such as protocol downgrade attacks and cookie hijacking. Therefore, this study aims to examine a web server based on SSL configuration and provide suggestions for a better and more secure SSL configuration. Testing in this study uses a program called SSLyze and this research produces a detailed report that can help to configure SSL on the Apache web server and Nginx web server properly and correctly in order to prevent further attacks. In addition to increasing security on the web server , using the right SSL configuration can make web server performance become optimal. The test results show that implementing the tested SSL configuration has a good level of security so that it can prevent security problems on the web server and can make web server performance become more optimal and efficient.